Teosentrisme dan Antroposentrisme dalam Al-Qur’an: Kajian Linguistik terhadap Dimensi Kalām dan Lisān - Abd. Moqsith; Salman Al Farisi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This study explores the epistemic tension between two interpretive orientations in Qur’anic scholarship: the theocentric view, which regards the Qur’an as kalām ilāhī (divine speech), and the anthropocentric perspective, which considers it as lisān—an Arabic linguistic product embedded in history and culture. While classical ʿulūm al-Qurʾān have largely emphasized the transcendent nature of divine speech, systematic investigation into the Qur’an as a historically situated linguistic structure remains underdeveloped. To address this gap, the present research proposes a synthetic approach that integrates both perspectives. Through linguistic analysis and contextual interpretation, this study demonstrates that the Qur’an simultaneously manifests as kalām—a mode of transcendent revelation—and as lisān—a temporally and spatially bound human language. This dual manifestation affirms the Qur’an’s nature as both divine and historical, universal and particular, transcendent and immanent. The findings offer a more integrative framework for Qur’anic studies, where linguistic inquiry and historical contextualization are essential not only for academic analysis but also for deepening theological understanding of revelation.